Effect of playing status and fixture congestion on training load, mental fatigue, and recovery status in premier league academy goalkeepers - Abbott, W.; Thomas, C.; Clifford, T. (The Journal of Strength and Conditioning Research, 2023)
Soccer goalkeepers are a unique playing position and require specific programming. Despite this, there is a paucity of information surrounding their support. The current investigation quantified internal and external training loads on and recovery status of starting and substitute academy goalkeepers during 1 and 2 match-weeks. Six professional soccer goalkeepers played the role of starting and substitute goalkeepers during both 1 and 2 match-weeks, providing data for 4 within-subject conditions (START-1, SUB-1, START-2, and SUB-2). Internal and external training load data were collected using ratings of perceived exertion and global positioning systems for all matches and training sessions. Physical and perceived recovery status was also collected daily for all individuals. Training load and recovery variables were analyzed across 4 playing conditions and 4 time points using a repeated measures analysis of variance. Results demonstrated significant differences in internal and external weekly training loads and physical and perceived recovery measures between starting and nonstarting goalkeepers. In the training leading up to matches, SUB-1 and SUB-2 had higher internal and external training loads compared with START-1. On a match-day, SUB-1 and SUB-2 performed more high-intensity actions but covered less total and high-speed distance than START-1. Following matches, substitutes had higher volumes of external training loads compared with START-1. The higher training loads experienced by substitutes at various time points resulted in lower physical recovery status on a match-day and post-match. START-1 demonstrated higher mental fatigue and lower well-being compared with substitute goalkeepers after match. The current investigation offers valuable insights for the preparation of professional goalkeepers.